The role of international marketing and promotion in the development of tourism, in case of Uzbekistan (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Promotions and marketing are critical in informing prospective worldwide market customers about appealing and convincing them to purchase a product. It also aids in drastically changing the behavior of existing clients in order to attract additional customers in order to ensure long-term success in starting a business and ensuring more earnings involved in the endeavor. tourist has been one of the most important sectors in Uzbekistan since the Middle Ages, but organized tourist planning began in the 1990s through different ways of planned growth. Uzbekistan's government saw tourism as a viable tool for growth and employment. Promotion and marketing guide Uzbekistan tourism through various market planning strategies such as the internet, newspaper advertisements, brochures, billboards, online advertisements, emails, and various social media platforms for the promotion of Uzbekistan's cultural heritage. For marketing tourism in the country, the Committe of Tourism launched a number of worldwide initiatives to portray Uzbekistan as an appealing, multi-cultural, contemporary, and sports-friendly destination. This will expose us to numerous concepts and goals of tourist promotion and marketing methods, as well as effective market management and environment. A sample of 27 respondents was obtained using a "standard questionnaire" constructed on a Google Form.